FAKTOR PENENTU FOREIGN DIRECT INVESTMENT DI ASEAN-7; ANALISIS DATA PANEL, 2000-2012 - Astrid Mutiara Ruth; Syofriza Syofyan (Media Ekonomi, 2014)
The number of Foreign Direct Investment (FDI) in Asia, especially in ASEAN, has been increasing drastically over the past few decades. FDI is one of the sources of investment that is really important, mainly for developing countries.This research aims to investigate what factors that determine FDI in ASEAN, during 2000-2012. ASEAN-7 (Indonesia, Singapore, Thailand, Malaysia, Vietnam, Laos, and Filipina) are the object of this research. This research is divided into two main parts. The first part is discussed about the determinant factors of FDI in ASEAN generally, and the second part is the partial analysis in each country, so it is expected to formulate the appropriate policy according to each condition.By using panel data analysis and STATA 11 as the software, it is seen that generally, factors determine FDI in ASEAN are the growth of GDP, interest rate, inflation rate, and trade openness. For Indonesia, FDI is influenced by the growth of GDP and inflation rate. The growth of GDP also affects FDI in Singapore, together with interest rate, trade openness, and depreciation rate of SGD, while, inflation rate and trade openness affect FDI in Thailand. In Malaysia, FDI is affected by the growth of GDP, inflation rate, and also trade openness.It is trade openness and depreciation rate that affect FDI in Vietnam. Meanwhile, in Laos, the growth of GDP and interest rate are factors determine FDI, and only inflation rate that influence FDI in Filipina.